PENGARUH INVESTASI, KEPEMILIKAN MANAJERIAL, DAN LEVERAGE OPERASI TERHADAP HUBUNGAN INTERDEPENDENSI ANTARA KEBIJAKAN DIVIDEN DENGAN KEBIJAKAN LEVERAGE KEUANGAN (Students' Journal of Accounting and Banking, 2013)
This study aimed to determine the effect of the investment, managerial ownership, and operating leverage on the relationship of interdependence between the dividend policy with the policy of financial leverage on the manufacturing companies listed on the Indonesia Stock Exchange (IDX). In this study, researchers used purposive sampling to the criteria of (1) the company remains actively operating and capital market activities do not stop until December 2011, (2) the company paying the dividends during the years of the study, (3) the necessary data regarding the factors to be studied presented complete. Obtained total sample of 135 companies of 578 manufacturing companies listed on the Stock Exchange. The data is then tested to normality, multicollinearity, heteroscedasticity, autocorrelation. The results showed that the study data are not normally distributed then do the normal data and outliers so free from the symptoms of classical assumptions. Further analysis researchers using Two Stage Least Square to test the research hypothesis. The results showed that in the first test model of investment and managerial ownership is not a significant effect on dividend policy, while operating leverage significant effect on dividend policy. And the second test model result that investment, managerial ownership, and operating leverage jointly insignificant effect on financial leverage. While the empirical results indicate that there is no interdependency relationship between dividend policy and financial leverage and the financial leverage and dividend policies. Keywords: Investment, Managerial Ownership, Operating Leverage, Dividend Policy, Operating Leverage.